A nucleotide-controlled conformational switch modulates the activity of eukaryotic IMP dehydrogenases - Rubén M. Buey (Nature Portfolio, 2017)
Abstract Inosine-5′-monophosphate dehydrogenase (IMPDH) is an essential enzyme for nucleotide metabolism and cell proliferation. Despite IMPDH is the target of drugs with antiviral, immunosuppressive and antitumor activities, its physiological mechanisms of regulation remain largely unknown. Using the enzyme from the industrial fungus Ashbya gossypii, we demonstrate that the binding of adenine and guanine nucleotides to the canonical nucleotide binding sites of the regulatory Bateman domain induces different enzyme conformations with significantly distinct catalytic activities. Thereby, the comparison of their high-resolution structures defines the mechanistic and structural details of a nucleotide-controlled conformational switch that allosterically modulates the catalytic activity of eukaryotic IMPDHs. Remarkably, retinopathy-associated mutations lie within the mechanical hinges of the conformational change, highlighting its physiological relevance. Our results expand the mechanistic repertoire of Bateman domains and pave the road to new approaches targeting IMPDHs.